The Manila Science High School an evaluative study - Cantero, Leticia L. 1927- (1979)
The subjects included 149 seniors, 289 graduates, 50 classroom teachers, and the school principal. Five kinds of data-gathering instruments were used: questionnaires, self-survey forms, psychological tests, a socio-economic status scale, and an accomplishment scale. The school has a systematic, effective program of recruitment of academically talented science potentials. The school curriculum provides a balanced program of science and non-science courses, and required elective, enrichment, and optional courses and has more science and mathematics courses than the revised general secondary curriculum but it utilizes community resources for curricular enrichment minimally.
Mimeographed.
Thesis (Ph.D.)--University of the Philippines, Los Banos.
Vita.
Keywords: Manila Science High School; High schools -- Philippines -- Manila